2018
DOI: 10.1111/ina.12468
|View full text |Cite
|
Sign up to set email alerts
|

Measuring public knowledge, attitudes, and behaviors related to radon to inform cancer control activities and practices

Abstract: Radon exposure is the second leading risk factor for lung cancer among smokers and the leading risk factor among non-smokers. Radon concentrated in lower levels of homes/buildings can be reduced if found, thus lowering lung cancer risk. The objective of this study was to measure radon knowledge in diverse populations, with varying radon-related laws, to inform radon-related cancer control practices and activities. A survey was mailed to 3000 homebuyers who purchased single-family homes; 995 responses (33%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Parents and guardians with more knowledge about radon were significantly more supportive of radon testing in schools. This is consistent with prior studies conducted in homeowners, which established that homeowners who knew the health risks associated with radon were more likely to have their homes tested (Duckworth et al, 2002;Ferng & Lawson, 1996;Ford et al, 1996;Howland, 1996;Neri et al, 2018). Our study builds on this finding by demonstrating that parents with a higher level of education are more supportive of regulating radon in schools in addition to homes.…”
Section: Discussionsupporting
confidence: 90%
“…Parents and guardians with more knowledge about radon were significantly more supportive of radon testing in schools. This is consistent with prior studies conducted in homeowners, which established that homeowners who knew the health risks associated with radon were more likely to have their homes tested (Duckworth et al, 2002;Ferng & Lawson, 1996;Ford et al, 1996;Howland, 1996;Neri et al, 2018). Our study builds on this finding by demonstrating that parents with a higher level of education are more supportive of regulating radon in schools in addition to homes.…”
Section: Discussionsupporting
confidence: 90%
“…These states could improve lung cancer prevention efforts (particularly for non-smokers) by working with local partners (e.g., real estate agents, builders, radon professionals, state radon program) that have existing knowledge of radon reduction efforts. Regardless of state policies, research has shown that people who report hearing of radonrelated health issues are 2-4 times more likely to test their home for radon, and including information on radon associations with cancer risk in cancer plans could increase awareness of this issue [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was defined as a human carcinogen by the International Agency for Research on Cancer (IARC) in 1988 and epidemiological studies ( 19 21 ) have successfully correlated radon exposure to lung cancer both in miner workers and other environmentally exposed populations ( 15 ). It is considered the second most important risk factor for the development of lung cancer after tobacco and the main risk factor amongst never smokers ( 22 ).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%